Development of molecularly imprinted biomimetic immunoassay method based on quantum dot marker for detection of phthalates. Issue 1 (1st January 2019) - Wang, Ximo; Chen, Chen; Xu, Longhua; Zhang, Hongyan; Xu, Zhixiang
ABSTRACT: In this study, a direct competitive molecularly imprinted biomimetic immunoassay method was developed for determination of the plasticizer dibutyl phthalate. Water-soluble carboxyl quantum dots were used as the marker. A hydrophilic molecularly imprinted polymer synthesized directly on the surface of a 96-well plate was used as biomimetic antibody. Under the optimal conditions, the limit of detection and the sensitivity of the method were 0.011 and 0.136 mg/L respectively. The cross-reaction values of two structural analogs were 4.75% and 6.89%, this indicaties that the method has the good specificity. Edible oil samples spiked with dibutyl phthalate were assayed, and good recoveries ranging from 80.0% to 111.5% were obtained. The method was used to detect dibutyl phthalate residues in liquors, and there were no significant differences obtained using the developed method and those obtained using gas chromatography.